BEHAVIOR OF PLASTIC TILES UNDER FLEXURE TEST AND ABRASION TEST (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The environmental decontamination and land pollution can be reduced by making best from waste. An alternative is provided for flooring or roofing tiles that consume nonrenewable resources, or produce negative environmental impact. In this research project three samples of tiles having 10 mm thickness were made. Waste Plastic from industries and epoxy resin along with hardner were mixed and tiles were casted. Then these tiles are tested in laboratory.